Implementation of Cloud Connected Smart Robot for Environmental and Industrial Platform - Senthil Kumar M.; V. Mathivanan (Institute of Advanced Engineering and Science, 2017)
Cloud robotics is an emerging field that is centred on the benefits of converged infrastructure and shared services of a cloud computing environment. In this paper, a system is designed with an autonomous Pick and Place robot to sense environmental data such as temperature and Motion, along with GPS coordinates and sends them on the cloud. The mobile robot is controlled using an LPC1764 microcontroller and communicates with the cloud via a CC3200 Launchpad. A private cloud is set up using Open Stack that provides Infrastructure as a Service. The collected data are stored in a cloud server which could be viewed through a mobile app and can be used to create awareness about the environmental changes of the location under study. A proof-of-concept prototype has been developed to illustrate the effectiveness of the proposed system.